Retrogression of ultrahigh-pressure eclogite, Western Gneiss Region, Norway - D. Spengler; A. Włodek; X. Zhong; A. Loges; S. J. Cuthbert (European Journal of Mineralogy, 2023)
The Western Gneiss Region (WGR) in western Norway exposes ultrahigh-pressure (UHP) eclogites that occur repeatedly, within an area of high-pressure (HP) eclogites, without evidence of being separated by tectonic shear or ductile flow structures. We studied 10 eclogites from two northern UHP areas and the interjacent HP area to evaluate the significance of this pattern. The orthopyroxene in orthopyroxene-bearing samples has low Al2O3 contents (0.17 wt %–0.37 wt %), provided its grain boundaries were unaffected by partial recrystallisation or replacement. Classical geothermobarometry based on element partitioning between coexisting mineral phases suggests metamorphic conditions within the diamond stability field for the samples from both the HP and UHP areas. The primary clinopyroxene in the associated orthopyroxene-free eclogites contains aligned inclusions of either needle-shaped quartz ± pargasite or lamellar albite, which are absent from the secondary (symplectic) clinopyroxene. Reconstructed mineral compositions of the primary clinopyroxene obtained from grain cross-section surfaces using a scanning electron beam or image processing are non-stoichiometric, and they have higher Ca-Eskola and lower Ca-Tschermak components than the inclusion-bearing host clinopyroxene. The molar ratios of these endmembers are consistent with the needles in the primary clinopyroxene being formed from vacancy-bearing precursor clinopyroxene by the exsolution reaction 2 Ca-Eskola = Ca-Tschermak + 3 quartz during early eclogite-facies retrogression. Further retrogression partially transformed the needle-shaped quartz to irregularly shaped albite within the clinopyroxene and partially transformed both clinopyroxene generations to amphibole that occasionally preserves the needles. The similarity of both the maximum metamorphic conditions and the mineral exsolution microstructures in the eclogites from UHP and HP areas indicates a shared metamorphic history within the stability field of diamond, but a history that diverged during retrogression. Consequently, the alternations of UHP and HP areas in the WGR may have formed by a process that allowed for spatial variations in retrogression efficiency, such as the localisation of strain (recrystallisation) or fluid flow (diffusion) or both, rather than by tectonic stacking of UHP and HP units. Evidence for the UHP metamorphism of WGR crustal rocks is now found from NE to SW along the entire coastal section that covers previously recognised UHP and interjacent areas.